Genetic Divergence in Indigenous Wild and Cultivated Rice Species of Manipur Valley. (1st November 2012) - Medhabati, K.; Rajiv Das, K.; Rohinikumar, M.; Sunitibala, H.; Dikash Singh, Th.
Abstract : Genetic divergence of 32 indigenous rice germplasms and five wild rice of which three from Manipur and two wild rice procured from IRRI, Philippines was investigated using Mahalanobis, D 2 statistic. Based on twelve agromorphological characters, the thirty-seven germplasms both wild and cultivated were grouped into five clusters based on the relative magnitudes of D 2 values following Tocher's method of cluster formation. Based on the rank totals, the characters which contributed maximum towards genetic divergence in the present studies were grain yield/plant, spikelet/panicle, 100 grain weight, grain length, days to 50% flowering, ear bearing tillers/plant, and flag leaf length. In the present study, maximum intercluster distance was estimated between cluster III and (D 2 = 14.09 ) which was closed followed by clusters II and V (D 2 = 12.50 ). On the basis of their greater intercluster distance, high value of cluster mean according to the character to be improved and performance of the individual germplasms for the character, the germplasms could be used in hybridization programme for improvement of different plant characters in the rice germplasms of Manipur.